Herbs as pharmaka: between Medicine, Astrology and Magic - Freni, Giulia (Studia Ceranea, 2023)
In the ancient and Byzantine world, natural elements were used to cure a certain disease, as attested by traditional medical sources such as Hippocrates, Dioscorides and Galen. However, the therapeutic properties of these substances are also described in some compilations that transmit another type of knowledge: the Cyranides, a hermetic work that illustrates the usages of vegetable, animal and mineral species for different purposes; Cassianus Bassus’ Geoponica, an important source of the ancient agronomic-botanical tradition; the Hygromanteia Salomonis, a hermetic and esoteric treatise dedicated to planetary divination, which also illustrates the correspondences between plants, planets and zodiac signs. The herbs described in these compilations are suggested as φάρμακα for the treatment of diseases, but also for other purposes such as warding off demons or having luck (e.g. in Monacensis gr. 70, which transmits Hygromanteia Salomonis, Jupiter’s plant is χρυσάγκαθον, capable of causing extraordinary healings). This denotes the development of a parallel medicine, connected with magic and astrology, and in some cases the practices discussed still have folkloric implications today. Therefore, this contribution intends to analyse these three magico- -medical works, highlighting the similarities and differences from traditional medical sources as well as the link between medicine, magic and astrology.